Diseño y construcción de sistemas CRISPRa y CRISPRi para el desarrollo de una terapia génica para el Parkinson (2020)
Parkinson's disease is the second most common neurodegenerative disease in the world. It affects 170 people per 100,000 inhabitants and is currently a relevant public health problem in older adults. Despite this, the usual treatments for this disease only treat the symptoms without impeding it's progress, which causes patients to deteriorate over time. Therefore, current approaches seek the development of new treatments based on neuronal proliferation and survival. Within these approaches, gene therapy is one of the most promising because it tries to provide the body with the ability to constantly generate the proteins necessary for treatment. Therefore, this work proposes the development of plasmids that contain CRISPRa and CRISPRi systems to alter gene expression and generate a disease-modifying treatment model. With this objective, the computational design and the initial steps of the molecular assembly were carried out for a therapy focused on the GDNF, PINK1 and PRKN genes.--Taken from the Degree Document Format.